Artesanato como exemplo de trabalho informal em uma região econômica periférica: uma análise geográfica do aglomerado produtivo de palhas e bordados da região norte do Piauí - Lima, Naíla Kelly do Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The lack of formal employment in localities with low economic growth and the existence of residents with lower level of education than labor market demands are factors that, linked to the need for survival, have resulted in constant increase search for informal and low-paid employment. This reality was observed through the study of the handicraft in North of Piauí, mainly using straw and needlework, due to the large amount of material available in nature and cultural tradition, passed through generations by diffusion of tacit knowledge. For being a significant economic activity in the region due to the income generation for hundreds of artisans and their families, usually beneficiaries of the social government program Bolsa Família, it had Federal and State government support from the 2000s, creating the most productive handicraft agglomeration of Piauí. Therefore, the developed research aimed to analyze the specifics of productive labor dynamics in the handicraft agglomeration production of North Piauí, focusing on informality. The research, carried out with the artisans and the presidents of the work associations, revealed that production output is almost entirely domestic, mainly by female work with family members help. Because it is an informal practice, the workers don‟t have labor rights, as fixed salary, retirement rights, vacation, accident insurance etc. Nowadays the absence of cooperation among the associations and the lack of technical support, managerial and financial, by public and private institutions prevent efficient governance and make the results fall short of the production capacity of artisans and the amount of material available in the region. As a result, the handicraft activity cannot be the only source of income, which leaves them economically vulnerable and keeps them subjugated by government assistance programs

A falta de emprego formal em localidades com baixo crescimento econômico e a existência de moradores com grau de instrução inferior ao que o mercado de trabalho exige são fatores que, atrelados à necessidade de sobrevivência dos mesmos, têm resultado na busca cada vez mais constante de ocupações informais e de baixa remuneração. No caso do Norte do Piauí, essa realidade pôde ser constatada por meio do estudo do artesanato, principalmente de palhas e bordados, devido à grande quantidade de matéria-prima disponível na natureza e da tradição cultural, passada de pai pra filho pela difusão de conhecimento tácito. Por ser uma atividade de significativa importância econômica para a região, pois gera renda para centenas de artesãos e suas famílias, geralmente beneficiários do Programa Bolsa Família, ela teve, a partir da década de 2000, incentivo do Governo Estadual e Federal, dando origem ao maior aglomerado produtivo de artesanato do Piauí. Em face dessa realidade, a pesquisa desenvolvida teve como objetivo analisar as especificidades das dinâmicas produtivas do trabalho no aglomerado produtivo de artesanato da região Norte do Piauí, com enfoque na informalidade. A investigação, realizada junto aos artesãos e aos presidentes das associações de trabalho revelou que a produção realizada é quase em sua totalidade doméstica, prevalecendo o trabalho feminino e com o auxílio de outros membros da família. Por se tratar de uma prática informal, o trabalhador não usufrui de direitos trabalhistas como, salário fixo, aposentadoria, férias, seguro contra acidentes etc. No que se refere ao aglomerado produtivo na atualidade, as ausências de cooperação entre as associações e de apoios técnico, gerencial e financeiro de instituições públicas e privadas inviabilizam uma governança eficiente e fazem com que os resultados estejam aquém da capacidade produtiva dos artesãos e da quantidade de matéria-prima...
Keywords: Economic geography; Geografia econômica; Artesanato; Economia regional; Arranjos produtivos locais; Trabalho informal; Trabalhos em palha; Piaui